Punishment, rewards and the importance of desert - Beade, Gustavo (Bergen Journal of Criminal Law & Criminal Justice, 2021)
We tend to think that if we are rewarded or punished, it is due to the fact that we deserve it – that we did something that merits such praise or blame. In this article, I am interested in its relationship with criminal responsibility and criminal punishment. Whilst desert is an important concept in criminal responsibility its importance is, at times, undeveloped. My aim in this work is not to reject desert or deny its importance in criminal punishment. Instead, I will rework the concept of desert defended mainly by retributivism. I will approach this issue by considering the problem of desert in relation to rewards and punishment. Furthermore, I distinguished between two particular ways in which desert plays different and important roles: formal desert and material desert.